Redirecting Human Rights - Grear, A. author. aut Link
XVII, 271 p.
Keywords: Against the backdrop of globalization and mounting evidence of the corporate subversion of the Universal Declaration of Human Rights paradigm, Anna Grear interrogates the complex tendencies within law that are implicated in the emergence of 'corporate humanity'. Grear presents a critical account of legal subjectivity, linking it with law's intimate relationship with liberal capitalism in order to suggest law's special receptivity to the corporate form. She argues that in the field of human rights law, particularly within the Universal Declaration of Human Rights paradigm, human embodied vulnerability should be understood as the foundation of human rights and as a key qualifying characteristic of the human rights subject. The need to redirect human rights in order to resist their colonization by powerful economic global actors could scarcely be more urgent.